Analisis Marketable Surplus Beras Merah - Salimah, Winada Fajar; Rachmina, Dwi; Dewi, Triana Gita (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
Rice farmers generally have a dual role, namely as producers and consumers of the rice produced. The consumption of farmer households with a marketable surplus is inversely related. This research aims to analyze the marketable surplus of brown rice and the factors that influence the marketable surplus of brown rice. The analysis used is descriptive analysis, marketable surplus calculation, and regression models. The research results show that the marketable surplus for brown rice, taking into account sumbang sokong, is relatively small, namely 11.56 percent. Meanwhile, the marketable surplus of brown rice without taking into account the contribution is 46.89 percent. The sumbang sokong tradition greatly influences the amount of marketable surplus because the large proportion of brown rice allocated for sumbang sokong (35.33 percent). The marketable surplus of brown rice is significantly and positively influenced by the land area. Thus, increasing market surplus can be done through expanding land by encouraging farmer motivation through increasing market access. Besides that, the rising of productivity can be conducted to push the marketable surplus.